Dharsono PEMANFAATAN JERAMI SEBAGAI PRODUK KREATIF NON INDUSTRIAL SEBAGAI DASAR PERTIMBANGAN DESAIN - Dharsono; Sumarno; N.R. Ardi Chandra (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2020)
Design plays an important role for product creation to have high aesthetic and economic value as an effort toempower the community. Important to be considered in the design is the ability of human resources andnatural resources related to straw. Therefore identifying the use of straw for various products and productiontechniques becomes important for planning in the development of industrial design. The research method is touse descriptive analytical research with data sources in the form of written, oral, related images. Data collectiontechniques with observation and data validity with data triangulation. Data analysis uses interactive analysis.The result of the discussion is that straw has been utilized as a variety of creative products, however theproduction is not yet industrial and there is no design development. Production capabilities and productiontechniques that develop in the community are important as a basis for the development of handicraft productsand industrial furniture.